High-strength, bend-resistant, lightweight aerospace special cable
Patent Information
- Application Number
- CN202611203457.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-23
AI Technical Summary
氟塑料虽具有优良的耐化学腐蚀性和阻燃性,但耐磨性和抗蠕变性能较差,且低温下易变脆;聚酰亚胺机械强度高、耐热性好,但加工困难、成本昂贵,且吸湿后介电性能下降;聚醚醚酮树脂综合性能优异,但其本身韧性不足,在反复大角度弯折工况下容易产生应力开裂,同时其阻燃等级尚难以满足高安全性场景的要求
本发明通过功能助剂的分子结构设计与多元素协同机制,在护套层中构建了刚柔并济的改性网络,结合磷、氮、硫多元素协同阻燃体系,在不大幅增加材料重量的前提下,有效平衡了护套层的拉伸强度、耐弯折柔韧性、阻燃性能及抗紫外老化能力,使线缆满足航空航天领域对高强度、耐弯折、轻量化和长寿命的综合要求。
Smart Images

Figure REF-OBJ-1786347505831-000001 
Figure REF-OBJ-1786347505831-000002
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cable technology, specifically, it relates to a high-strength, bend-resistant, lightweight aerospace special cable. Background Technology
[0002] Aerospace-grade special cables are key components ensuring the safe and reliable operation of aircraft electrical systems. Their performance directly affects the operational stability and flight safety of airborne equipment in extreme environments. With the rapid development of the aviation industry towards high maneuverability, long endurance, and lightweight design, increasingly stringent requirements are being placed on the mechanical strength, resistance to repeated bending, flame retardancy, and aging life of cables. Currently, common aerospace cable sheathing materials mainly include high-performance polymers such as fluoroplastics, polyimide, and polyetheretherketone (PEEK). While fluoroplastics possess excellent chemical corrosion resistance and flame retardancy, their abrasion resistance and creep resistance are poor, and they easily become brittle at low temperatures. Polyimide has high mechanical strength and good heat resistance, but it is difficult to process, expensive, and its dielectric properties decrease after absorbing moisture. PEEK resin has excellent overall performance, but its inherent toughness is insufficient, making it prone to stress cracking under repeated large-angle bending conditions. Furthermore, its flame retardancy rating is still insufficient to meet the requirements of high-safety scenarios.
[0003] To improve flame retardant properties, existing technologies typically add halogenated or phosphorus-containing small-molecule flame retardants to the sheath matrix. However, these additives have poor compatibility with the matrix resin and are prone to migration and precipitation. This not only reduces the long-term stability of the material but also causes localized stress concentration due to agglomeration, thus weakening the tensile strength and flexural fatigue resistance of the material. Furthermore, traditional flame retardant modification often comes at the cost of sacrificing the material's flexibility and lightweight, making it difficult to simultaneously improve mechanical properties, flame retardancy, and aging resistance. Regarding UV aging resistance, commonly used sheath materials are prone to molecular chain breakage and yellowing under strong UV radiation, affecting the cable's service life. Adding UV absorbers, however, presents the problem of migration and volatilization.
[0004] Therefore, how to endow the sheath layer with excellent strength, flexibility, flame retardancy and anti-aging ability without significantly increasing the weight, while ensuring a good balance between the various properties, is a technical problem that urgently needs to be solved in the field of aerospace special cables. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a high-strength, bend-resistant, lightweight aerospace special cable.
[0006] The objective of this invention can be achieved through the following technical solutions: A high-strength, bend-resistant, lightweight aerospace special cable includes a conductor, an epoxy-coated inner layer sprayed on the outside of the conductor, and a sheath layer covering the outside of the inner layer; the sheath layer includes the following components: by weight, 50-70 parts polyetheretherketone resin, 40-50 parts low-density polyethylene, 2-3 parts lubricant, 1-2 parts antioxidant, 8-10 parts functional additives, 5-8 parts talc, 4-5 parts nano-silica, and 1-2 parts silane coupling agent.
[0007] In a more optimized manner, the preparation process of the functional additive is as follows: S1: Under a protective atmosphere, sulfathiazole, terephthalaldehyde, and anhydrous toluene were mixed, the temperature was raised to 120°C, and the mixture was refluxed for 6 hours. Then the temperature was lowered to 85°C, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was slowly added in batches. After the addition was complete, the temperature was raised back to 120°C, and the mixture was refluxed for another 20 hours. After the reaction was completed, the mixture was naturally cooled to room temperature, concentrated under reduced pressure to about half of the original volume, allowed to stand, and filtered after the solid was fully separated. The filter cake was washed with a small amount of anhydrous toluene, then washed with petroleum ether, and dried under vacuum to constant weight to obtain intermediate A. S2: Under a protective atmosphere, intermediate A, dimeric long-chain aliphatic diamine, anhydrous dichloromethane, and tetrahydrofuran are mixed and stirred until homogeneous. The temperature is then raised to 70°C. After the reaction is complete, the mixture is cooled to room temperature under a protective atmosphere, and the solvent is removed by vacuum distillation. The residue is purified by silica gel column chromatography, eluted with a dichloromethane / methanol mixed solvent, and the product fraction is collected. The solvent is then removed by vacuum drying to obtain the functional additive.
[0008] This method utilizes a nucleophilic addition-dehydration condensation reaction between the primary amino group on sulfathiazole and an aldehyde group in a terephthalaldehyde molecule to generate a single Schiff base structure, thus retaining the other aldehyde group as a subsequent reaction site. Subsequently, the active PH bond in 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) reacts with the aforementioned imine double bond under heating conditions, introducing the phosphaphenanthrene flame-retardant group into the molecular backbone, yielding intermediate A containing a free aldehyde group. Then, the remaining aldehyde group on intermediate A undergoes another Schiff base condensation reaction with the two terminal amino groups of a dimerized long-chain aliphatic diamine, forming a bis-Schiff base structure with a long-chain aliphatic hydrocarbon as a bridging group, ultimately yielding the target functional additive. In this structure, the long-chain methylene segment of the dimerized long-chain aliphatic diamine acts as a flexible link, providing a freely rotating buffer unit between the rigid DOPO aromatic ring, sulfathiazole ring, and benzene ring skeleton. This results in a large number of flexible buffer points after the material is cured, effectively absorbing the impact energy of external forces and significantly improving the toughness of the material. At the same time, the DOPO phosphorus-phenanthrene group can release phosphorus-containing free radicals during combustion to capture active free radicals in the gas phase and promote char formation in the condensed phase. The sulfur and nitrogen heteroatoms in sulfathiazole can synergistically catalyze char formation, enhancing the density of the char layer, thereby endowing the material with excellent flame retardant properties.
[0009] The structure of the functional additive is shown below:
[0010] In a more optimized manner, in step S1, the ratio of the amounts of sulfathiazole, terephthalaldehyde, anhydrous toluene, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 12.77 g: 6.71 g: 100 mL: 10.81 g.
[0011] In a more optimized manner, in step S2, the ratio of intermediate A, dimeric long-chain aliphatic diamine, anhydrous dichloromethane, and tetrahydrofuran is 23.5g:10.9g:65mL:65mL.
[0012] More preferably, the type of the dimer long-chain aliphatic diamine is Priamine 1074.
[0013] More preferably, the antioxidant is antioxidant 1010.
[0014] Ideally, the lubricant is polyethylene wax.
[0015] Ideally, the silane coupling agent is γ-aminopropyltriethoxysilane.
[0016] The beneficial effects of this invention are: This invention constructs a rigid-flexible modified network in the sheath layer through the molecular structure design of functional additives and the multi-element synergistic mechanism. Combined with a phosphorus, nitrogen, and sulfur multi-element synergistic flame retardant system, it effectively balances the tensile strength, bending flexibility, flame retardant performance, and UV aging resistance of the sheath layer without significantly increasing the material weight. This enables the cable to meet the comprehensive requirements of the aerospace field for high strength, bending resistance, lightweight, and long life.
[0017] Regarding tensile strength, the long-chain methylene segments introduced by the dimerized long-chain aliphatic diamine in the functional additive molecules serve as flexible connecting units. These segments can form freely rotating buffer regions between the rigid DOPO phosphenanthrene groups, sulfathiazole rings, and benzene ring backbone. These flexible segments can effectively intercalate within the cross-linked network of the sheath matrix composed of polyetheretherketone resin and low-density polyethylene, forming numerous molecular-level flexible nodes. Simultaneously, the rigid aromatic and heterocyclic units in the molecular structure provide load-bearing support, maintaining the dimensional stability of the material under tension. Furthermore, the talc and nano-silica added to the formulation, as inorganic reinforcing fillers, improve the interfacial bonding with the matrix resin after surface treatment with a silane coupling agent, promoting uniform filler dispersion and reducing internal defects caused by agglomeration, thereby effectively improving the tensile strength of the sheath layer.
[0018] In terms of bending resistance and flexibility, the synergistic effect of the flexible chain segments and the rigid skeleton enables the sheath layer to maintain high strength while possessing excellent flexibility. During external bending or torsion, the flexible units effectively absorb and dissipate fracture energy through chain segment slippage and conformational deformation, avoiding the propagation of microcracks caused by stress concentration. This gives the sheath layer excellent resistance to repeated bending and allows it to maintain structural integrity even under large-angle torsion conditions.
[0019] In terms of flame retardant properties, the DOPO phosphorus-containing groups in the functional additives decompose under high temperature or flame conditions, releasing phosphoric acid-containing substances that catalyze the dehydration of the sheath matrix into char, forming a dense char layer on the surface. The nitrogen and sulfur heteroatoms in the sulfathiazole structure release nitrogen-containing inert gases during pyrolysis, diluting the concentration of combustible vapors and oxygen in the combustion zone, while also participating in the cross-linking reaction of the char layer, further improving the density and graphitization degree of the char layer. The synergistic effect of phosphorus, nitrogen, and sulfur through two pathways—promoting char formation in the condensed phase and diluting combustible gases in the gas phase—gives the sheath layer excellent flame retardant properties, effectively inhibiting the spread of combustion.
[0020] In terms of UV aging resistance, the phosphoranone group of DOPO in the functional additive molecule and the Schiff base conjugated structure formed by the condensation of sulfathiazole and terephthalaldehyde both have UV absorption capabilities, which can effectively shield UVA and UVB band ultraviolet light, reduce resin molecular chain breakage and yellowing aging caused by ultraviolet radiation. Combined with the antioxidant 1010 added to the formula, it can further synergistically inhibit the thermo-oxidative aging process and extend the service life of the cable.
[0021] In summary, this invention effectively improves the overall performance of the sheath layer in terms of high strength, bending resistance, flame retardancy, and UV aging resistance without significantly increasing the weight of materials, thus meeting the stringent requirements for cables in the aerospace field. Detailed Implementation
[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0023] Example 1: A high-strength, bend-resistant, lightweight aerospace special cable, comprising a conductor (nickel-plated aluminum alloy conductor), an epoxy-coated inner layer (0.12 mm thick, epoxy resin particle size 100 mesh) sprayed on the outside of the conductor, and a sheath layer covering the outside of the inner layer; the sheath layer comprises the following components: by weight, 50 parts polyetheretherketone resin, 40 parts low-density polyethylene, 2 parts lubricant (polyethylene wax), 1 part antioxidant (antioxidant 1010), 8 parts functional additives, 5 parts talc, 4 parts nano silica, and 1 part silane coupling agent (γ-aminopropyltriethoxysilane). Its preparation method is as follows: (1) The aluminum alloy conductor is subjected to a series of pretreatment processes, including chemical degreasing, hot water washing, cold water washing, and acid pickling activation, to remove surface oil and oxide layer; then a continuous electroplating process is used to deposit a nickel layer on the surface of the aluminum alloy conductor to obtain a nickel-plated aluminum alloy conductor, wherein the thickness of the nickel layer is 5μm. (2) An electrostatic powder spraying process is used to uniformly spray epoxy resin powder with a particle size of 100 mesh onto the surface of nickel-plated aluminum alloy conductor; after spraying, it is sent to a curing oven for heating and curing treatment. The curing temperature is 200℃ and the curing time is 15min, so that the epoxy resin powder melts and flows and undergoes a cross-linking reaction, forming an epoxy spraying inner layer with a thickness of 0.12mm on the conductor surface. (3) The raw materials of the sheath layer are put into a high-speed mixer and stirred evenly to obtain the sheath layer mixture; the mixture is directly added to the hopper of a single screw extruder, heated, melted and plasticized, and then extruded through the die head mold onto the outside of the epoxy spray inner layer. After cooling and shaping, the finished product is obtained. The preparation process of the functional additives is as follows: S1: Under a protective atmosphere, 12.77 g of sulfathiazole, 6.71 g of terephthalaldehyde, and 100 mL of anhydrous toluene were mixed, the temperature was raised to 120 °C, and the mixture was refluxed for 6 h. Then the temperature was lowered to 85 °C, and 10.81 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was slowly added in batches. After the addition was complete, the temperature was raised back to 120 °C, and the mixture was refluxed for another 20 h. After the reaction was completed, the mixture was naturally cooled to room temperature, concentrated under reduced pressure to about half of the original volume, allowed to stand, and filtered after the solid was fully separated. The filter cake was washed with a small amount of anhydrous toluene, then washed with petroleum ether, and dried under vacuum to constant weight to obtain intermediate A. S2: Under a protective atmosphere, 23.5 g of intermediate A, 10.9 g of dimerized long-chain aliphatic diamine (Priamine 1074), 65 mL of anhydrous dichloromethane, and 65 mL of tetrahydrofuran were mixed and stirred until homogeneous. The temperature was then raised to 70 °C. After the reaction was completed, the mixture was cooled to room temperature under a protective atmosphere, and the solvent was removed by vacuum distillation. The residue was purified by silica gel column chromatography, eluted with a dichloromethane / methanol mixed solvent, and the product fraction was collected. The solvent was removed by vacuum distillation, and the product was dried to obtain the functional additive.
[0024] Example 2: A high-strength, bend-resistant, lightweight aerospace special cable, comprising a conductor (nickel-plated aluminum alloy conductor), an epoxy-coated inner layer (0.12 mm thick, epoxy resin particle size 100 mesh) sprayed on the outside of the conductor, and a sheath layer covering the outside of the inner layer; the sheath layer comprises the following components: by weight, 70 parts polyetheretherketone resin, 50 parts low-density polyethylene, 3 parts lubricant (polyethylene wax), 2 parts antioxidant (antioxidant 1010), 10 parts functional additives, 8 parts talc, 5 parts nano silica, and 2 parts silane coupling agent (γ-aminopropyltriethoxysilane). Its preparation method is as follows: (1) The aluminum alloy conductor is subjected to a series of pretreatment processes, including chemical degreasing, hot water washing, cold water washing, and acid pickling activation, to remove surface oil and oxide layer; then a continuous electroplating process is used to deposit a nickel layer on the surface of the aluminum alloy conductor to obtain a nickel-plated aluminum alloy conductor, wherein the thickness of the nickel layer is 5μm. (2) An electrostatic powder spraying process is used to uniformly spray epoxy resin powder with a particle size of 100 mesh onto the surface of nickel-plated aluminum alloy conductor; after spraying, it is sent to a curing oven for heating and curing treatment. The curing temperature is 200℃ and the curing time is 15min, so that the epoxy resin powder melts and flows and undergoes a cross-linking reaction, forming an epoxy spraying inner layer with a thickness of 0.12mm on the conductor surface. (3) The raw materials of the sheath layer are put into a high-speed mixer and stirred evenly to obtain the sheath layer mixture; the mixture is directly added to the hopper of a single screw extruder, heated, melted and plasticized, and then extruded through the die head mold onto the outside of the epoxy spray inner layer. After cooling and shaping, the finished product is obtained. The preparation process of the functional additives is as follows: S1: Under a protective atmosphere, 12.77 g of sulfathiazole, 6.71 g of terephthalaldehyde, and 100 mL of anhydrous toluene were mixed, the temperature was raised to 120 °C, and the mixture was refluxed for 6 h. Then the temperature was lowered to 85 °C, and 10.81 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was slowly added in batches. After the addition was complete, the temperature was raised back to 120 °C, and the mixture was refluxed for another 20 h. After the reaction was completed, the mixture was naturally cooled to room temperature, concentrated under reduced pressure to about half of the original volume, allowed to stand, and filtered after the solid was fully separated. The filter cake was washed with a small amount of anhydrous toluene, then washed with petroleum ether, and dried under vacuum to constant weight to obtain intermediate A. S2: Under a protective atmosphere, 23.5 g of intermediate A, 10.9 g of dimerized long-chain aliphatic diamine (Priamine 1074), 65 mL of anhydrous dichloromethane, and 65 mL of tetrahydrofuran were mixed and stirred until homogeneous. The temperature was then raised to 70 °C. After the reaction was completed, the mixture was cooled to room temperature under a protective atmosphere, and the solvent was removed by vacuum distillation. The residue was purified by silica gel column chromatography, eluted with a dichloromethane / methanol mixed solvent, and the product fraction was collected. The solvent was removed by vacuum distillation, and the product was dried to obtain the functional additive.
[0025] Example 3: A high-strength, bend-resistant, lightweight aerospace special cable, comprising a conductor (nickel-plated aluminum alloy conductor), an epoxy-coated inner layer (0.12 mm thick, epoxy resin particle size 100 mesh) sprayed on the outside of the conductor, and a sheath layer covering the outside of the inner layer; the sheath layer comprises the following components: by weight, 60 parts polyetheretherketone resin, 45 parts low-density polyethylene, 2.5 parts lubricant (polyethylene wax), 1.5 parts antioxidant (antioxidant 1010), 9 parts functional additives, 6.5 parts talc, 4.5 parts nano silica, and 1.5 parts silane coupling agent (γ-aminopropyltriethoxysilane); Its preparation method is as follows: (1) The aluminum alloy conductor is subjected to a series of pretreatment processes, including chemical degreasing, hot water washing, cold water washing, and acid pickling activation, to remove surface oil and oxide layer; then a continuous electroplating process is used to deposit a nickel layer on the surface of the aluminum alloy conductor to obtain a nickel-plated aluminum alloy conductor, wherein the thickness of the nickel layer is 5μm. (2) An electrostatic powder spraying process is used to uniformly spray epoxy resin powder with a particle size of 100 mesh onto the surface of nickel-plated aluminum alloy conductor; after spraying, it is sent to a curing oven for heating and curing treatment. The curing temperature is 200℃ and the curing time is 15min, so that the epoxy resin powder melts and flows and undergoes a cross-linking reaction, forming an epoxy spraying inner layer with a thickness of 0.12mm on the conductor surface. (3) The raw materials of the sheath layer are put into a high-speed mixer and stirred evenly to obtain the sheath layer mixture; the mixture is directly added to the hopper of a single screw extruder, heated, melted and plasticized, and then extruded through the die head mold onto the outside of the epoxy spray inner layer. After cooling and shaping, the finished product is obtained. The preparation process of the functional additives is as follows: S1: Under a protective atmosphere, 12.77 g of sulfathiazole, 6.71 g of terephthalaldehyde, and 100 mL of anhydrous toluene were mixed, the temperature was raised to 120 °C, and the mixture was refluxed for 6 h. Then the temperature was lowered to 85 °C, and 10.81 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was slowly added in batches. After the addition was complete, the temperature was raised back to 120 °C, and the mixture was refluxed for another 20 h. After the reaction was completed, the mixture was naturally cooled to room temperature, concentrated under reduced pressure to about half of the original volume, allowed to stand, and filtered after the solid was fully separated. The filter cake was washed with a small amount of anhydrous toluene, then washed with petroleum ether, and dried under vacuum to constant weight to obtain intermediate A. S2: Under a protective atmosphere, 23.5 g of intermediate A, 10.9 g of dimerized long-chain aliphatic diamine (Priamine 1074), 65 mL of anhydrous dichloromethane, and 65 mL of tetrahydrofuran were mixed and stirred until homogeneous. The temperature was then raised to 70 °C. After the reaction was completed, the mixture was cooled to room temperature under a protective atmosphere, and the solvent was removed by vacuum distillation. The residue was purified by silica gel column chromatography, eluted with a dichloromethane / methanol mixed solvent, and the product fraction was collected. The solvent was removed by vacuum distillation, and the product was dried to obtain the functional additive.
[0026] Comparative Example 1: No functional additives were added, as follows: A high-strength, bend-resistant, lightweight aerospace-grade special cable includes a conductor (nickel-plated aluminum alloy conductor), an epoxy-coated inner layer (0.12 mm thick, epoxy resin particle size 100 mesh) sprayed on the outside of the conductor, and a sheath layer covering the outside of the inner layer; the sheath layer includes the following components: by weight, 60 parts polyetheretherketone resin, 45 parts low-density polyethylene, 2.5 parts lubricant (polyethylene wax), 1.5 parts antioxidant (antioxidant 1010), 6.5 parts talc, 4.5 parts nano silica, and 1.5 parts silane coupling agent (γ-aminopropyltriethoxysilane); Its preparation method is as follows: (1) The aluminum alloy conductor is subjected to a series of pretreatment processes, including chemical degreasing, hot water washing, cold water washing, and acid pickling activation, to remove surface oil and oxide layer; then a continuous electroplating process is used to deposit a nickel layer on the surface of the aluminum alloy conductor to obtain a nickel-plated aluminum alloy conductor, wherein the thickness of the nickel layer is 5μm. (2) An electrostatic powder spraying process is used to uniformly spray epoxy resin powder with a particle size of 100 mesh onto the surface of nickel-plated aluminum alloy conductor; after spraying, it is sent to a curing oven for heating and curing treatment. The curing temperature is 200℃ and the curing time is 15min, so that the epoxy resin powder melts and flows and undergoes a cross-linking reaction, forming an epoxy spraying inner layer with a thickness of 0.12mm on the conductor surface. (3) The raw materials of the sheath layer are put into a high-speed mixer and stirred evenly to obtain the sheath layer mixture; the mixture is directly added to the hopper of a single screw extruder, heated, melted and plasticized, and then extruded through the die head mold onto the outside of the epoxy spray inner layer. After cooling and shaping, the finished product is obtained.
[0027] Comparative Example 2: An excessive amount of functional additives was added, as detailed below: A high-strength, bend-resistant, lightweight aerospace-grade special cable includes a conductor (nickel-plated aluminum alloy conductor), an epoxy-coated inner layer (0.12 mm thick, epoxy resin particle size 100 mesh) sprayed on the outside of the conductor, and a sheath layer covering the outside of the inner layer; the sheath layer includes the following components: by weight, 60 parts polyetheretherketone resin, 45 parts low-density polyethylene, 2.5 parts lubricant (polyethylene wax), 1.5 parts antioxidant (antioxidant 1010), 15 parts functional additives, 6.5 parts talc, 4.5 parts nano silica, and 1.5 parts silane coupling agent (γ-aminopropyltriethoxysilane). Its preparation method is as follows: (1) The aluminum alloy conductor is subjected to a series of pretreatment processes, including chemical degreasing, hot water washing, cold water washing, and acid pickling activation, to remove surface oil and oxide layer; then a continuous electroplating process is used to deposit a nickel layer on the surface of the aluminum alloy conductor to obtain a nickel-plated aluminum alloy conductor, wherein the thickness of the nickel layer is 5μm. (2) An electrostatic powder spraying process is used to uniformly spray epoxy resin powder with a particle size of 100 mesh onto the surface of nickel-plated aluminum alloy conductor; after spraying, it is sent to a curing oven for heating and curing treatment. The curing temperature is 200℃ and the curing time is 15min, so that the epoxy resin powder melts and flows and undergoes a cross-linking reaction, forming an epoxy spraying inner layer with a thickness of 0.12mm on the conductor surface. (3) The raw materials of the sheath layer are put into a high-speed mixer and stirred evenly to obtain the sheath layer mixture; the mixture is directly added to the hopper of a single screw extruder, heated, melted and plasticized, and then extruded through the die head mold onto the outside of the epoxy spray inner layer. After cooling and shaping, the finished product is obtained. The preparation process of the functional additives is as follows: S1: Under a protective atmosphere, 12.77 g of sulfathiazole, 6.71 g of terephthalaldehyde, and 100 mL of anhydrous toluene were mixed, the temperature was raised to 120 °C, and the mixture was refluxed for 6 h. Then the temperature was lowered to 85 °C, and 10.81 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was slowly added in batches. After the addition was complete, the temperature was raised back to 120 °C, and the mixture was refluxed for another 20 h. After the reaction was completed, the mixture was naturally cooled to room temperature, concentrated under reduced pressure to about half of the original volume, allowed to stand, and filtered after the solid was fully separated. The filter cake was washed with a small amount of anhydrous toluene, then washed with petroleum ether, and dried under vacuum to constant weight to obtain intermediate A. S2: Under a protective atmosphere, 23.5 g of intermediate A, 10.9 g of dimerized long-chain aliphatic diamine (Priamine 1074), 65 mL of anhydrous dichloromethane, and 65 mL of tetrahydrofuran were mixed and stirred until homogeneous. The temperature was then raised to 70 °C. After the reaction was completed, the mixture was cooled to room temperature under a protective atmosphere, and the solvent was removed by vacuum distillation. The residue was purified by silica gel column chromatography, eluted with a dichloromethane / methanol mixed solvent, and the product fraction was collected. The solvent was removed by vacuum distillation, and the product was dried to obtain the functional additive.
[0028] Testing experiment: (1) The tensile strength of the cable sheath layer of the embodiments and comparative examples was tested in accordance with standard GB / T 1040.1-2025; (2) The oxygen index of the cable sheaths of the examples and comparative examples was determined by high temperature test according to standard GB / T 2406.3-2022; (3) At room temperature, fix one end of the cable of the example and the comparative example on the fixed clamp of the testing machine and the other end on the rotating clamp. Set the torsion angle (±180°), the speed (30 times / min), and the target number of times (100,000 times). Start the testing machine to ensure that the cable axis coincides with the torsion axis. During the test, stop the machine every 10,000 times to check: observe whether there is cracking in the appearance; evaluate whether it passes after the test. Evaluation criteria: no cracks or twisting on the surface of the sample. (4) At 6000 μw / cm 2 The tensile strength change rate was measured after 10 days of ultraviolet irradiation. The obtained data is shown in the table below:
[0029] Conclusion: The high-strength, bend-resistant, lightweight aerospace special cables provided in this invention achieve a significant synergistic improvement in mechanical properties, flame retardancy, UV aging resistance, and bend flexibility by adding functional additives with specific structures to the sheath layer. Test results from Examples 1 to 3 show that the tensile strength of the sheath layer reaches 86.2-91.5 MPa, the oxygen index reaches 31.6%-33.6%, and the tensile strength change rate after high-intensity UV irradiation is only -7.1% to -8.3%. All cables can pass ±180°C, 100,000 cycles of room temperature torsion testing, indicating that while maintaining high strength, they possess excellent flexibility and fatigue crack resistance, while also exhibiting outstanding flame retardancy and aging resistance. In comparison, Comparative Example 1, without the addition of functional additives, showed a significant decrease in tensile strength (69.8 MPa), oxygen index (22.8%), and strength retention rate after UV aging, and failed the torsion test, indicating that functional additives are indispensable for improving the overall performance of the system. Although Comparative Example 2 added an excessive amount of functional additives (15 parts), the oxygen index was improved (32.6%), but the tensile strength (75.6 MPa) and the change rate after UV aging (-10.4%) were still lower than those of the example. In particular, the torsion test was also failed, indicating that excessive functional additives would lead to an excessive increase in the rigidity of the sheath layer and an overly dense flexible buffer node, which would deteriorate the bending resistance.
[0030] In summary, this invention, through the design of a flexible and rigid molecular structure in the functional additives and the synergistic flame-retardant mechanism of phosphorus, nitrogen, and sulfur, combined with suitable inorganic fillers and coupling agents, effectively balances the tensile strength, bending flexibility, flame retardant properties, and UV aging resistance of the sheath layer without significantly increasing the weight. This enables the cable to meet the stringent comprehensive requirements of the aerospace field for high strength, bending resistance, lightweight, and long life. Furthermore, its formulation range is reasonable, demonstrating good practicality and promotional value.
[0031] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0032] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A high-strength, bend-resistant, lightweight aerospace special cable, characterized in that, It includes a conductor, an epoxy sprayed inner layer applied to the outside of the conductor, and a sheath layer covering the outside of the inner layer; the sheath layer includes the following components: by weight, 50-70 parts polyetheretherketone resin, 40-50 parts low-density polyethylene, 2-3 parts lubricant, 1-2 parts antioxidant, 8-10 parts functional additives, 5-8 parts talc, 4-5 parts nano silica, and 1-2 parts silane coupling agent.
2. The high-strength, bend-resistant, lightweight aerospace special cable according to claim 1, characterized in that, The preparation process of the functional additive is as follows: S1: Under a protective atmosphere, sulfathiazole, terephthalaldehyde, and anhydrous toluene were mixed, the temperature was raised to 120°C, and the mixture was refluxed for 6 hours. Then the temperature was lowered to 85°C, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was slowly added in batches. After the addition was complete, the temperature was raised back to 120°C, and the mixture was refluxed for another 20 hours. After the reaction was completed, the mixture was naturally cooled to room temperature, concentrated under reduced pressure to about half of the original volume, allowed to stand, and filtered after the solid was fully separated. The filter cake was washed with a small amount of anhydrous toluene, then washed with petroleum ether, and dried under vacuum to constant weight to obtain intermediate A. S2: Under a protective atmosphere, intermediate A, dimeric long-chain aliphatic diamine, anhydrous dichloromethane, and tetrahydrofuran are mixed and stirred until homogeneous. The temperature is then raised to 70°C. After the reaction is complete, the mixture is cooled to room temperature under a protective atmosphere, and the solvent is removed by vacuum distillation. The residue is purified by silica gel column chromatography, eluted with a dichloromethane / methanol mixed solvent, and the product fraction is collected. The solvent is then removed by vacuum drying to obtain the functional additive.
3. The high-strength, bend-resistant, lightweight aerospace special cable according to claim 2, characterized in that, In step S1, the ratio of the amounts of sulfathiazole, terephthalaldehyde, anhydrous toluene, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 12.77 g: 6.71 g: 100 mL: 10.81 g.
4. The high-strength, bend-resistant, lightweight aerospace special cable according to claim 2, characterized in that, In step S2, the ratio of intermediate A, dimeric long-chain aliphatic diamine, anhydrous dichloromethane, and tetrahydrofuran is 23.5g:10.9g:65mL:65mL.
5. A high-strength, bend-resistant, lightweight aerospace special cable according to claim 2, characterized in that, The type of the dimerized long-chain aliphatic diamine is Priamine 1074.
6. The high-strength, bend-resistant, lightweight aerospace special cable according to claim 1, characterized in that, The antioxidant is antioxidant 1010.
7. The high-strength, bend-resistant, lightweight aerospace special cable according to claim 1, characterized in that, The lubricant is polyethylene wax.
8. A high-strength, bend-resistant, lightweight aerospace special cable according to claim 1, characterized in that, The silane coupling agent is γ-aminopropyltriethoxysilane.